Perilaku Lentur Balok Beton Menggunakan Geotextile pada Daerah Tarik - Sri Ponny; Jonie Tanijaya; Suryanti Rapang Tonapa (Paulus Civil Engineering Journal, 2021)
Geotextile is made of permeable geosynthetic. Geotextile s are formed from synthetic fibers based on polymers that have high mechanical properties in tensile strength, trapezoidal tearing strength, and puncture resistance. Therefore, researchers want to increase the use of Geotextile as an added material in the tensile area of concrete blocks. The test objects used are 9 pieces of 150mm×150mm×600mm beams. The results of the research were that the addition of woven Geotextile s and non-woven Geotextile s on concrete blocks increased, for woven Geotextile s by 21.593% of beams without using Geotextile s and non-woven Geotextile s of 17.058% of beams without using Geotextile s. So the use of Geotextile s on concrete blocks can improve quality because the value of the flexural strength of beams using Geotextile s is greater than beams without using Geotextiles.